Intervention Program to Increase Parental Acceptance of Children with Special Needs - Safitri, Fathia Afrazayne; Kurniawati, Farida (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Condition of special need child can affect parental acceptance, thus affecting the parenting practice and development of special need child. Various intervention programs with various methods have been developed to increase parental acceptance towards special need child. Based on this phenomenon this systematic literature review was conducted to give details of intervention programs that have been found could increase parental acceptance towards special need child. There are 5 studies used in this systematic literature review that has been screened from 5 online databases, namely Taylor & Francis, ScienceDirect, SpringerLink, Google Scholar, and PubMed. Participants were parents of special need children, including Intellectual Disability (ID), Deaf, Autism, Pervasive Development Disorder (PDD), and Cerebral Palsy (CP). The result of this systematic literature review shows that understanding of special need child, religious approach, as well as awareness of parents’ emotions can help increase parental acceptance towards special need child. Method that can be used in delivering intervention materials including lectures, questions and answer, video, self-reflection, case study, and “homework”. Result of discussion from systematic literature review can provide scientific references for development of intervention programs for parental acceptance towards special need child.Kondisi anak berkebutuhan khusus dapat memengaruhi penerimaan orang tua. Penerimaan orang tua memengaruhi pengasuhan yang diterapkan dan perkembangan anak berkebutuhan khusus. Program intervensi dengan berbagai metode pun dikembangkan untuk meningkatkan penerimaan orang tua terhadap anak berkebutuhan khusus. Berdasarkan hal ini tinjauan pustaka sistematis dapat membantu menggambarkan program intervensi dalam meningkatkan penerimaan orang tua terhadap anak berkebutuhan khusus. Terdapat 5 studi yang dikaji dari hasil penyaringan lima basis data daring, yakni Taylor & Francis, ScienceDirect, SpringerLink, Google Scholar, dan PubMed. Partisipan merupakan orang tua dari anak berkebutuhan khusus, yang meliputi disabilitas intelektual, Tuli, Autisme, Pervasive Development Disorder (PDD), dan Cerebral Palsy (CP). Tinjauan pustaka sistematis menunjukkan bahwa pemahaman terkait anak berkebutuhan khusus, pendekatan melalui agama, serta kesadaran orang tua terhadap emosi membantu meningkatkan penerimaan terhadap anak berkebutuhan khusus. Metode yang dapat digunakan dalam proram intervensi pun antara lain ceramah, tanya-jawab, video, refleksi diri, studi kasus, dan “pekerjaan rumah”. Hasil pembahasan dari tinjauan pustaka sistematis dapat memberikan referensi ilmiah dalam pengembangan program intervensi penerimaan orang tua terhadap anak berkebutuhan khusus.